2011
DOI: 10.1590/s1516-35982011001200015
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sperm characteristics and testosterone in bovine seminal plasma by direct radioimmunoassay

Abstract: The objectives of this study were to validate a non-extractive RIA for seminal testosterone and quantify the hormone using a solid-phase commercial kit, and study the correlation between testosterone in seminal plasma and sperm characteristics. Parallelism showed a correlation index r = 0.992 (Y = -5.47 + 1.073X; R² = 0.985), indicating that the non-extractive method presented is indicated particularly for assessment of testosterone when establishing comparisons between samples. Overall mean (±SD) of testoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In humans, seminal T concentration can be both positively or negatively correlated with sperm quality 14,42 . In nellore bulls ( Bos indicus ) there was a negative correlation of seminal T concentration with the number of sperm deficits 43 , but another study found no such correlations at all 44 . In birds, the literature is very scarce: In domestic chickens ( Gallus gallus domesticus ), testosterone may induce negative effects on sperm metabolic rate.…”
Section: Discussionmentioning
confidence: 94%
“…In humans, seminal T concentration can be both positively or negatively correlated with sperm quality 14,42 . In nellore bulls ( Bos indicus ) there was a negative correlation of seminal T concentration with the number of sperm deficits 43 , but another study found no such correlations at all 44 . In birds, the literature is very scarce: In domestic chickens ( Gallus gallus domesticus ), testosterone may induce negative effects on sperm metabolic rate.…”
Section: Discussionmentioning
confidence: 94%
“…However, results of the present study did not support their findings. Earlier studies also reported that the circulating blood testosterone concentrations are not related to libido ( Schallenberger et al, 1991 ; Sekasiddhi and Buban, 1997 ) and semen quality ( Souza et al, 2011 ) or have only low correlation with mass activity and motility ( Santos et al, 2004 ; Souza et al, 2011 ). Since testosterone concentration varies with many factors like species, breed, individual, age, season, environmental conditions and time, frequent estimation of testosterone in short intervals taken with objective measures of other traits may be necessary to accurately assess relationships of testosterone concentrations with seminal characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…Testes productivity in producing spermatozoa is dependent upon the numbers of spermatogonia cells performed mitosis and meiosis cleavages [5], and testes ability to produce testosterone [7]. The higher testosterone concentration the better production of substrates are responsible for regulating and performing spermatogenesis activity [8,9,10]. Some studies have analyzed the relationship between serum testosterone concentration, sperms quality and fertility of bulls, and some of them reported a strong correlation [11,12,13], but other could not find any association [10].…”
Section: Introductionmentioning
confidence: 99%